Populist Success in a Hung Parliament: The 2018 General Election in Italy. Issue 4 (2nd October 2018) - Chiaramonte, Alessandro; Emanuele, Vincenzo; Maggini, Nicola; Paparo, Aldo
ABSTRACT: The 2018 Italian general elections were a crucial test to assess the resilience of mainstream parties vis-à-vis the challenge provided by populist forces and the stabilisation of the tripolar party system emerged in 2013. The article analyses the outcome of the election, whose most remarkable result was the unprecedented success of two populist parties, the M5S and the Lega, by focusing on key aspects such as the new electoral system, the coalition-building process, the electoral campaign, the evolution of the Italian party system, and the analysis of vote shifts between parties.